Overexpression of annexin 1 in pancreatic cancer and its clinical significance - Bai, Xiao-Feng (World J Gastroenterol, 2004)
AIM: To investigate the expression of annexin I in pancreatic cancer and its relationship with the clinicopathologic factors, and to evaluate its potential clinical significance. METHODS: Annexin I expression was analyzed by Western blot and immunohistochemical staining in pancreatic adenocarcinoma and multi-tissue microarrays (MTAs). RESULTS: Western blot analysis showed that annexin I was overexpressed in 84.6% (11/13) pancreatic ductal adenocarcinomas. Immunohistochemistry analysis of pancreatic cancer in MTAs showed that annexin I protein was 71.4% (30/42) positive which was markedly increased compared with that in the tumor matched normal pancreas tissues 18.4% (7/38) (P < 0.01). In the meantime, the high expression of annexin 1 was correlated with the poor differentiation of pancreatic adenocarcinoma. CONCLUSION: Annexin 1 overexpression is a frequent biological marker and correlates with the differentiation of pancreatic cancer during tumorigenesis.